PERAN LEMBAGA KURSUS DAN PELATIHAN MENJAHIT DALAM MEMPERKUAT MANAJEMEN PEMBERDAYAAN MASYARAKAT DI DESA PADALARANG - erwin rifal fauzi; Novi Widiastuti,M.Pd (Comm-Edu (Community Education Journal), 2018)
Social problems that exist in the community become the background in this research. Social problems are an inseparable part of social life in society, which ultimately affects society itself. The impact also varies, namely the disparity between social classes and the increase of unemployment rate, community empowerment done by government and private. LKP among others is trying to contribute in helping solve social problems in the community. The development of LKP in Indonesia is very rapid, reaching approximately 20,152 the LKP year 2107 in Indonesia according to the information of Directorate of Training and Training Course. including in West Bandung which reached 35 LKP according to KBB course info. with these programs aim to provide knowledge, skills, skills, life skills, and attitudes to self-development, professional development, work, independent business, and/or continuing education to a higher level. And the purpose of this research is to know how the role of Special Institution and Training of Sewing in Strengthening the Management of Community Empowerment.